2011
DOI: 10.1007/s00248-010-9801-8
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota Was Assessed in Cirrhotic Patients with Hepatitis B Virus Infection

Abstract: To unravel the profile of intestinal microecological parameters in Chinese patients with asymptomatic carriage of hepatitis B virus (HBV), chronic hepatitis B, decompensated HBV cirrhosis, and health controls and to establish their correlation with liver disease progression, we performed quantitative PCR and immunological techniques to investigate fecal parameters, including population of fecal predominant bacteria and the abundance of some virulence genes derived from Escherichia coli, Bacteroides fragilis, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
195
6
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(216 citation statements)
references
References 44 publications
12
195
6
3
Order By: Relevance
“…While the B/E ratio from this study was lower in patients with liver cirrhosis than that in the healthy group, suggesting that the intestinal colonization resistance was reduced in cirrhotic patients. Similar results were reported by other author [24].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…While the B/E ratio from this study was lower in patients with liver cirrhosis than that in the healthy group, suggesting that the intestinal colonization resistance was reduced in cirrhotic patients. Similar results were reported by other author [24].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, real-time PCR was utilized to obtain a quantitative estimation of the Enterobacteriaceae, Enterococcus, and Bifidobacterium genus in the two groups. The results revealed that Enterobacteriaceae and Enterococcus increased dramatically in the cirrhotic group, which corresponded with some current reports on liver damage [22,24]. This investigation on alternation may shed some light on the pathological mechanism of liver cirrhosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Дегидроксилирование желчных кислот [33,56] [43,59,61,63]. Несмотря на то, что печень не находится в непосредственном контакте с живыми мик-роорганизмами, населяющими желудочно-кишечный тракт, безоговорочным является тот факт, что любые нарушения микробиоце-ноза кишечника оказывают неизбежно отри-цательное влияние на патофизиологическое и морфофункциональное состояние печени вследствие воздействия микробных патоген-ассоциированных молекулярных паттернов (PAMPs) -эндотоксинов (липополисахаридов), бактериальных метаболитов, а также бактери-альной ДНК и компонентов клеточной стенки [48].…”
Section: Clostridium Cluster Xivaunclassified
“…12 Another report indicated a progressive decrease in the ratio of Bifidobacterium to Enterobacteriaceae accompanying progression of liver disease in a range of subjects, from healthy controls to subjects with decompensated hepatitis B virus cirrhosis to asymptomatic carriers and subjects with chronic hepatitis B. 13 This indicates that changes in gut microbiota seem to mirror changes in severity of disease. The TLR 4/lipopolysaccharide interaction may be the link modulating this relationship; the role of this interaction in fibrogenesis is increasingly recognized.…”
Section: Microbiota and Liver Diseasementioning
confidence: 99%